Pengaruh Penggunaan Metode Strorytelling berbantuan Video Animasi Untuk Meningkatkan keterampilan Bercerita Siswa Kelas V - Novi Alpiani (JPT : Jurnal Pendidikan Tematik, 2025)
This study aims to determine the effect of the storytelling method assisted by animated videos on the storytelling skills of fifth grade elementary school students. This research used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The sample consisted of 40 students, 20 in the experimental group and 20 in the control group. Data were collected through storytelling skill tests (posttest) and analyzed using the Kolmogorov-Smirnov normality test and independent t-test. The results showed a significant difference between the experimental and control groups, with a significance value of 0.000 < 0.05. This indicates that the storytelling method assisted by animated videos significantly affects the improvement of students' storytelling skills.